Metodologi Penulisan Bulugh Al-Maram Sebagai Kitab Hadith Al-Ahkam - Hj. Sulaiman, Ishak (Jurnal Usuluddin, 1999)
Kitab Bulugh al-Maram is regarded as a source of reference of Hadith al-Ahkam and written by Ibn Hajar al- 'Asqalani, a Hadith scholar who lived in the 8th century of Hijrah. This article is focused on Bulugh al-Maram's methodology including the contents and arrangement of each book and chapter, and also the use of specific terms for its Hadith.